Pulmonary Oncology—Scope of the Pulmonologist - Tandon, Sandeep; Biraris, Pavankumar; Bhaskar, Maheema (Indian Journal of Medical and Paediatric Oncology, 2022)
The International Agency for Research on Cancer GLOBOCAN project has predicted that India's cancer burden will nearly double in the next 20 years, from slightly more than a million new cases in 2012 to more than 1·7 million by 2035. In India, chronic respiratory diseases have emerged as a leading health care burden with chronic obstructive pulmonary disease (COPD) being the second leading cause of deaths and disability-adjusted life years. Patients with COPD are 6.35 times more likely to develop lung cancer. The deadly dual epidemic of “chronic respiratory diseases and cancer” warrants not only prevention but also creating an increased awareness among oncologists as well as pulmonologists to enable early diagnosis and treatment. It would be incorrect to assume that the scope of a pulmonologist in oncology is just diagnosing and treating lung cancer or prescribing chemotherapy for lung cancer. There is a larger world full of opportunities beyond that, and we look at the pulmonologist as a member of a multidisciplinary oncology team working together with the surgical, radiation, and medical oncologist and ancillary specialties to address all the issues highlighted earlier that are faced in oncology practice. The current exposure to pulmonary oncology and related complications during postgraduate training for respiratory medicine in India is limited. It is necessary not only to educate the pulmonologist on their role in an oncology setup but also to increase the awareness across all oncology specialties regarding the pulmonologist's contribution in management of the cancer patient. In this review, written based on our experience gained in our pulmonology service in our tertiary oncology center, we have tried to portray the wide role of the pulmonologist in oncology. We have realized that what is lacking is the basic awareness regarding the above potential, both among pulmonologists and oncologists. Our mission is to take this message across specialists in India, highlighting how we can work synergistically in the fight against cancer.
Keywords: pulmonology; pulmonary oncology; pulmonologist; thoracic oncology